UFO registry: final analysis of baseline data from patients with advanced prostate cancer in Asia - Dingwei Ye; Ravindran Kanesvaran; Edmund Chiong; Bannakij Lojanapiwat; Yeong-Shiau Pu; Sudhir Kumar Rawal; Ong Teng Aik; Hao Zeng; Byung Ha Chung; Md Yusoff Noor Ashani; Chikara Ohyama; Choung Soo Kim; et al. (Therapeutic Advances in Medical Oncology)
Background: The incidence of prostate cancer (PC) is increasing in Asian countries. The epidemiology of PC, its treatment including the use of novel therapeutic options, impacts on quality of life, and clinical outcomes of patients with PC in Asia, are not well documented. Objectives: To describe the demographic and disease features of the full cohort of patients enrolled in the United in Fight against prOstate cancer (UFO) registry. Design: The UFO registry was a multi-national, longitudinal, observational study of patients with PC presenting to participating tertiary care hospitals in eight Asian countries/regions. Methods: Patients with high-risk localized PC (HRL), non-metastatic biochemically recurrent, or metastatic PC were consecutively enrolled from September 14, 2015 until September 1, 2020 and followed for up to 5 years. Results: Among the full cohort of 3635 patients, 425 had HRL, 389 had non-metastatic biochemically recurrent, and 2821 had metastatic PC. Median follow-up time was 4.2, 4.2, and 2.6 years, respectively. At first diagnosis, the mean age ranged from 65.7 to 69.1 years, 38.5% had extra-capsular tumor extension, 34.0% had regional lymph node metastases, and 65.1% had distant metastases. Quality-of-life scores at enrollment were significantly worse in patients with metastatic disease. Decisions to start therapy were mainly driven by treatment guidelines and disease progression. The decision to discontinue hormonal therapy was often due to disease progression. Few patients received novel hormonal therapies despite their availability. Conclusion: The UFO registry provides a detailed, contemporary picture of the characteristics, treatment, and outcomes of patients with PC in Asia. There is an unmet medical need to improve access to novel agents in Asia, aiming to improve quality of life and clinical outcomes. Trial registration: Clinicaltrials.gov Identifier: NCT02546908, Registry Identifier: NOPRODPCR4001.